2015
DOI: 10.1080/00387010.2014.933355
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and Ultraviolet Spectroscopic Evaluation of Phenolic Compounds, Antioxidant and Binding Activities in Some Kiwi Fruit Cultivars

Abstract: Spectrophotometric assays (Folin-Ciocalteu, ferric-reducing=antioxidant power, cupric-reducing antioxidant capacity, and b-carotene linoleate model system) have been used to evaluate the total phenolics and flavonoids in kiwi fruit cultivars in ethanol and water extracts. Fluorescent and infrared measurements were correlated with the obtained spectroscopic data. It was found that the contents of the bioactive compounds and the level of antioxidant activity in different extracts differ significantly (p < 0.05).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…3a, Jinlong had the highest level of antioxidants (95.95%), and Jinxiang had the lowest (93.64%) in the peel of kiwi fruit powder. The observed values were similar to those reported by Bernardes et al (2011) for the pulp and skin of kiwi fruit (96.09% and 95.69%, respectively) and by Park et al (2015) for kiwi fruit in nature (92.90%). The antioxidant activity using the ABTS method (Fig.…”
Section: Determination Of Total Phenolic Compounds and Total Flavonoidssupporting
confidence: 92%
“…3a, Jinlong had the highest level of antioxidants (95.95%), and Jinxiang had the lowest (93.64%) in the peel of kiwi fruit powder. The observed values were similar to those reported by Bernardes et al (2011) for the pulp and skin of kiwi fruit (96.09% and 95.69%, respectively) and by Park et al (2015) for kiwi fruit in nature (92.90%). The antioxidant activity using the ABTS method (Fig.…”
Section: Determination Of Total Phenolic Compounds and Total Flavonoidssupporting
confidence: 92%
“…In addition, anthocyanins and proanthocyanidin exist in grape (He et al, 2016a,b,c;Lingua et al, 2016), and hesperidin is commonly found in orange and pomelo (Pereira-Caro et al, 2015). The main polyphenols of kiwifruit were identified as derivatives of coumaric, caffeic acids containing chlorogenic acid, quinic acid and caffeoyl-glucoside, and flavonols were present as sinensetin (Dawes & Keene, 1999;Park et al, 2015;Izli et al, 2017). The flavonoids and their derivatives are the most abundant polyphenol in OJ, including the naringenin, naringenin-trisaccharide, luteolin-rutinoside, hesperetin-rutinoside and a type of flavanone (quercetin-trisaccharide).…”
Section: Individual Phenolic Compounds Of Fruit Juices During In Vitrmentioning
confidence: 99%
“…5a). In our previous study, the IR spectra data showed that the main bands in the kiwi fruit samples slightly shifted (Park et al 2015c). IR spectrum of polyphenols showed common peaks for all kiwi fruit samples at 3299-3300 cm −1 , 2924-2930 cm −1 , 1232-1235 cm −1 , and 919-924 cm −1 , except cultivar 'M 1 ' (Fig.…”
Section: Fourier Transform Infrared Spectra Of Polyphenolsmentioning
confidence: 73%
“…'Bidan,' a new cultivar of A. eriantha, was selected in South Korea. The average fruit weight is 25 g. The cultivar 'Bidan' has high content of vitamin C and antioxidative activity compared to the A. deliciosa cultivar 'Hayward' (Jo et al 2007;Park et al 2013;Li et al 2014;Park et al 2015c). Three major allergenic proteins of kiwi fruits, such as kiwellin (Tamburrini et al 2005;Tupo et al 2008;Maddumage at al.…”
Section: Introductionmentioning
confidence: 99%